Fabrication of cellulose acetate /citric acid composite electrospun nanofibers and their antibacterial activities - Faried, Mohamed Adly (AUC Knowledge Fountain, 2015)
In an attempt to develop novel natural nanofibers with enhanced antimicrobial activities, polymer composites and nanomaterials play a vital role and exhibit superior properties. Among the different types of nanomaterials, nanofibers have attracted a lot of attention in various fields due to their large surface area per unit mass and advanced mechanical performance. Nanofibers are potential candidates to be used in many fields such as drug delivery systems, nano-sensors, filtration media, and medical applications, etc. Among theses applications is the use of these nannanofibers in wound management. The development of novel approaches that can enhance wounds healing is always in focus of research. Here in our research, we're trying to develop an effective, safe and economic composite nanofibers with an antimicrobial activity that can have an application as a novel wound dressing that can enhance healing. The main objectives of this thesis are: (i) to prepare and optimize the fabrication of Cellulose Acetate (CA) nanofibers by Electrospinning technique, (ii) to add Citric acid (CIT) as an antimicrobial material to the formed electrospun CA nanofibers and (iii) to finally investigate a possible enhancement in the antibacterial activity of the electrospun composite CA/CIT nanofibers against two different bacterial strains; Escherichia coli (E. Coli) and Staphylococcus aureus (S. aureus). In this study, electrospinning technique was used and the experimental parameters were optimized to fabricate uniform CA electrospun nanofibers as well as CA/CIT composite nanofibers to be tested for their antimicrobial activities. Electrospinning parameters (such as applied voltage, and solution flow rate, distance from the spinneret tip-to-the collector and the solvent system) of CA and CA/CIT blend solutions were varied to be electrospun to choose the most acceptable electrospinning conditions. The most uniform nanofibers were obtained with 5% (w/v) for CA dissolved in acetone at voltage 15 KV, at a tip-collector distance of 5 cm and a solution flow rate of 5mL/hr. Thereafter, these parameters were used with CA/CIT blend solution (5% CA and 10% CIT in acetone) in order to obtain uniform and bead free electrospun CA/CIT composite nanofibers. After successful preparation of electrospun CA and CA/CIT composite nanofibers, full characterization of the morphology and chemical structural characteristics by using scanning electron microsopy (SEM) and Fourier Transform Infrared (FT-IR) spectroscopy were carried out. After characterization of the produced CA and CA/CIT Electrospun nanofibers, they were tested for their antibacterial activity with E. coli and Staphylococcus aureus (S. aureus) bacteria, by the dynamic contact method. Amazingly, the negative control (E.coli) showed an increase in the bacterial growth from zero to 48 hours by 26.5% (i.e. from 1.06 x 108 to 2.8 x 109 CFU), respectively, while on the other hand, the electrospun CA nanofibers showed only 2.2% increase in the bacterial growth at the same time interval (from 1.09 x 108 to 2.4 x 108 CFU), respectively. Similarly, the negative control (S. aureus) showed an increase in the bacterial growth from zero to 48 hours by 28% (i.e. from 1.09 x 108 to 3.08 x 109 CFU), respectively, while on the other hand, the electrospun CA nanofibers showed only 2.1% increase in the bacterial growth at the same time interval (from 1.1 x 108 to 2.34 x 108 CFU), respectively. Moreover, CA/CIT electrospun composite nanofibers showed much higher antibacterial activities (i.e. lower growth rate) than CA electrospun nanofibers and also the negative control against both bacterial strains. So, in case of E-coli, the CA/CIT electrospun composite nanofibers showed only 1.5% increase in the bacterial growth at the same time interval (from 1.3 x 108 to 1.98 x 108 CFU), respectively. Similarly, in case of S-aureus, the CA/CIT electrospun composite nanofibers showed only 1.46% increase in the bacterial growth at the same time interval (from 1.15 x 108 to 1.69 x 108 CFU), respectively. These results open new avenues for fabricating antibacterial products from semi synthetic materials with superior biomedical activities. Additionally, trials to electrospin other composites of CA, namely CA/CS & CA/CS/CIT were done, however no nanofibers could be obtained.